Recurrent toxin-mediated erythema in a 6-year-old boy. - Molka, Ben Salem; Anissa, Zaouak; Houda, Hammami; Samy, Fenniche (European Journal of Pediatric Dermatology, 2025)
Toxin-mediated erythema is an uncommon cutaneous manifestation of group A β-hemolytic streptococcal (GAS) infection, resulting from the systemic action of streptococcal pyrogenic exotoxins rather than local bacterial invasion. We describe a 6-year-old boy with recurrent pharyngitis who developed sharply demarcated erythema of the perineal region, extending to the thighs and inguinal folds. Throat culture grew GAS, while perineal swabs were sterile. Both pharyngitis and rash resolved rapidly after oral amoxicillin therapy. This was the third recurrence. Differential diagnoses included Kawasaki disease, scarlet fever, and perianal streptococcal dermatitis. The temporal association with pharyngitis, negative local culture, and rapid antibiotic response supported a toxin-mediated mechanism. This is, to our knowledge, the first documented Tunisian case of recurrent toxin-mediated erythema. Recognition of this entity is essential to ensure prompt treatment and to avoid unnecessary investigations in children presenting with perineal erythema.